2010
DOI: 10.1186/1744-859x-9-30
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the emotional responses produced by exposure to real food, virtual food and photographs of food in patients affected by eating disorders

Abstract: BackgroundMany researchers and clinicians have proposed using virtual reality (VR) in adjunct to in vivo exposure therapy to provide an innovative form of exposure to patients suffering from different psychological disorders. The rationale behind the 'virtual approach' is that real and virtual exposures elicit a comparable emotional reaction in subjects, even if, to date, there are no experimental data that directly compare these two conditions. To test whether virtual stimuli are as effective as real stimuli,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
133
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(141 citation statements)
references
References 25 publications
6
133
0
2
Order By: Relevance
“…Those participants who experienced smoking-related VEs as though they were in real-life situations showed higher levels of craving than participants who did not feel a sufficient sense of presence in the virtual situations. These results are in line with those of previous research in which a high level of experienced sense of presence was related to a stronger reactivity in participants on being exposed to virtual cues (Bordnick et al, 2008;Gorini, Griez, Petrova, & Riva, 2010;Robillard, 2003). Among the other variables analyzed, only the FTND score showed predictive power for smoking craving.…”
Section: Discussionsupporting
confidence: 82%
“…Those participants who experienced smoking-related VEs as though they were in real-life situations showed higher levels of craving than participants who did not feel a sufficient sense of presence in the virtual situations. These results are in line with those of previous research in which a high level of experienced sense of presence was related to a stronger reactivity in participants on being exposed to virtual cues (Bordnick et al, 2008;Gorini, Griez, Petrova, & Riva, 2010;Robillard, 2003). Among the other variables analyzed, only the FTND score showed predictive power for smoking craving.…”
Section: Discussionsupporting
confidence: 82%
“…Ferrer-García et al [24] found that, compared with controls, patients with ED showed significantly higher levels of anxiety and depressed mood in virtual environments that were meaningful and relevant to their disorder, such as ones where they had eaten a virtual food or visited the swimming pool. Another study comparing emotional reactions to real food, VR food, and photographs of food in ED patients and healthy control participants found that real and VR food produced comparable emotional reactions in ED patients, with this reaction being even stronger than the one produced by photographs of food [25]. The results obtained with both in vivo and VR exposure appear to be similar, which indicates that these environments could be used for both evaluative and therapeutic aims.…”
Section: Discussionmentioning
confidence: 94%
“…In recent years, studies have shown that exposure to virtual food produces the same sensations as exposure to real food, using both non-immersive [24] and immersive environments [25].…”
Section: Virtual Reality As a Clinical Toolmentioning
confidence: 99%
“…For example, Gorini, Griez, Petrova and Riva [40] found that, for ED patients, virtual food was as anxiety provoking as real food and more so than pictures of food. Others have demonstrated that virtual environments involving high-caloric food elicit strong emotional responses in ED patients [41], reflecting a fear of gaining weight and an over-evaluation of weight and shape.…”
Section: Efficacy Of Virtual Reality Focusing On Body Image In Ed Womenmentioning
confidence: 99%